Pyonephrosis due to congenital obstruction - Rizki Usaputro; I Made Suyadnya (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2024)
Pyonephrosis is a suppurative infection of the upper urinary tract due to a combination of obstruction and hydronephrosis of the high urinary tract. Patients usually come with flank pain and fever with or without enlargement of abdomen. Pyonephrosis may lead to a urosepsis condition that can cause life threatening conditions if timely non-treated with antibiotics and surgical intervention. We report uncommon 2 cases of 16 years old female with pyonephrosis due to Ureteropelvic Obstruction and 21 years old female with pyonephrosis due to Ureterovesical Junction (UVJ) Obstruction. Clinical features, work up diagnosis and management of the pyonephrosis with the review of literature have been discussed here.